ANALISIS PENANAMAN KARAKTER PERCAYA DIRI ANAK USIA 4-5 TAHUN MELALUI METODE BERMAIN PERAN DI TK ADE IRMA SURYANI SCHOOL - Juliana; Novita Friska; Aminda Tri Handayani; Juli Yanti Harahap (STKIP Subang, 2026)
The problem in this study is the low level of self-confidence among children aged 4–5 years at TK Ade Irma Suryani School. This is caused by their lack of courage to interact with classmates and their low level of participation during learning activities. The purpose of this study is to analyze the development of self-confidence character in children aged 4–5 years through the role-playing method at TK Ade Irma Suryani School. The research method used is qualitative, employing a descriptive qualitative approach as a procedure or method to solve the research problem. Based on the results of the study, the implementation of the role-playing method had a positive effect on developing self-confidence in children aged 4–5 years at TK Ade Irma Suryani School. The children showed behavioral changes such as being more confident in speaking, answering teachers’ questions, and being able to play roles according to the characters assigned. Therefore, it can be concluded that role-playing activities can effectively enhance the self-confidence character of children aged 4–5 years at TK Ade Irma Suryani School.